Block-based design for low noise amplifiers - Perlez, Don Lawrence
The project provides a design methodology for Low Noise Amplifiers (LNAs) that employs block-based implementation. Each ideal component from the circuit level design is replaced by a 2-port component consisting of the s-parameter data of a commercially available component. S-parameters, Noise Figure and Gain are the basis of comparison for the circuit level and block-based implementation. Given the s-parameters, component Quality factors are obtained. Using the component's q-factor, the project determines the actual response and performance of the designs, thus when actual parameters are used, a more accurate simulation is achieved. The project is able to characterize both the 2.4GHz and 5GHz LNA Designs for optimum Noise Figure and specified Gain using different s-parameters of actual components. The effects of s-parameters and quality factor to the LNA designs varied along with the component's non-idealities and actual parameters. LNA performance of actual components' Q-factors is compared with the performance of ideal components with the same Q-factor. Results show -90% simulation accuracy.